2003
DOI: 10.1182/blood-2002-07-2072
|View full text |Cite
|
Sign up to set email alerts
|

The human herpes virus 8–encoded viral FLICE inhibitory protein protects against growth factor withdrawal–induced apoptosis via NF-κB activation

Abstract: The human herpes virus 8 (HHV8)-encoded viral FLICE (Fas-associating protein with death domain-like interleukin-1-converting enzyme) inhibitory protein (vFLIP) is believed to protect cells against death receptor-mediated apoptosis. In the present study we demonstrate that expression of HHV8 vFLIP in a growth factor-dependent TF-1 leukemia cell line protects against growth factor withdrawal-induced apoptosis. Unlike vector-expressing cells, those expressing HHV8 vFLIP maintain their mitochondrial membrane poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 46 publications
4
79
0
Order By: Relevance
“…The human herpesvirus 8 is linked to Kaposi's sarcoma and primary effusion lymphoma. Its v-FLIP protein suppresses apoptosis triggered by growth factor deprivation by persistently activating the IKK kinase complex thereby inducing expression of Bcl-xL (Liu et al, 2002;Sun et al, 2003). Lastly, gammaherpesviruses establish latent infections in lymphocytes and are implicated in nasopharyngeal carcinoma, Kaposi's sarcoma and B-cell lymphomas.…”
Section: Implication Of Nf-kb In the Cell Response To Viral Infectionmentioning
confidence: 99%
“…The human herpesvirus 8 is linked to Kaposi's sarcoma and primary effusion lymphoma. Its v-FLIP protein suppresses apoptosis triggered by growth factor deprivation by persistently activating the IKK kinase complex thereby inducing expression of Bcl-xL (Liu et al, 2002;Sun et al, 2003). Lastly, gammaherpesviruses establish latent infections in lymphocytes and are implicated in nasopharyngeal carcinoma, Kaposi's sarcoma and B-cell lymphomas.…”
Section: Implication Of Nf-kb In the Cell Response To Viral Infectionmentioning
confidence: 99%
“…Phosphorylated IB␣ has been used as a surrogate for the activation of NF-B, because it constitutes a key step in the release of NF-B subunits and eventual nuclear translocation (17,18). Moreover, a variable response to BCR signaling in CLL cells has been reported previously (33,50,51) and linked to the presence of decreased levels of functionally relevant adhesion molecules, cell-signaling receptors, and 11q22-q23 deletion (16).…”
Section: Discussionmentioning
confidence: 99%
“…Here we have investigated the correlation of the presence of phosphorylated IB␣ (p-IB␣), a marker of NF-B activation (17,18), with changes in the expression profile and clinical outcome of CLL cases.…”
Section: Introductionmentioning
confidence: 99%
“…However, we have subsequently shown that K13 is a strong inducer of the NF-kB pathway through the activation of the IkB kinase complex and does not function as a caspase-8 inhibitor (Chaudhary et al, 1999;Liu et al, 2002;Matta et al, 2003;Matta and Chaudhary, 2004;Chugh et al, 2005). We and others have further shown that K13 utilizes the NF-kB pathway to promote cellular transformation, cytokine secretion and protection against growth-factor withdrawal-induced apoptosis Sun et al, 2003aSun et al, , b, 2006. We were interested in examining the effect of K13 on vascular endothelial cells, as it is one of the few HHV8-encoded proteins to be expressed in latently infected KS spindle cells and, therefore, is an ideal candidate for inducing spindle cell phenotype in HHV8-infected endothelial cells.…”
mentioning
confidence: 92%